Effect of techniques, trays and materials on accuracy of impressions clinically made - Messias, Aion Mangino; Silva, Stephania Caroline Rodolfo; Abi-rached, Filipe De Oliveira; Souza, Raphael Freitas; Reis, José Maurício Dos Santos Nunes (Universidade Estadual Paulista Júlio de Mesquita Filho, 2019)
AbstractIntroduction Making accurate and dimensionally stable impressions to duplicate oral conditions and tooth morphology is an essential step of prosthetic dentistry for fabricating well-fitted indirect restorations and, consequently, ensure the longevity and success of the treatment. Several authors describe pros and cons of different impression techniques, although there is no unanimity among them about the best one.Objective This study evaluated casts’ accuracy made by different impression techniques, trays and materials.Material and method 10 patients were selected and 20 impressions from teeth #13 to #16 were performed using single-step (SS) and two-step techniques, made with metal stock and customized acrylic resin partial trays, vinyl polysiloxane and condensation silicone rubbers. Type IV gypsum was used to pour the casts. Three photographs of each patient (baseline), as their respective gypsum casts, were taken, measured in their interested buccal surface area. Comparisons of area values among experimental groups and baseline were performed. Data showed adherence to normal curve, being submitted to 3-way ANOVA/Bonferroni test (α=.05).Result Technique produced significant differences (P=0.02). SS technique was more accurate than BUR one (P=0.003; 95=1.22 to 5.98), but both resulted in similar casts to PVC, MOV and NR techniques, which were similar to each other (P>0.05).Conclusion SS technique showed the closest absolute values to baseline.

ResumoIntrodução Realizar moldagens precisas e dimensionalmente estáveis que dupliquem a condição oral é um passo essencial para a confecção de restaurações indiretas de qualidade, garantindo seu sucesso e longevidade. Diversos estudos tem demonstrado os prós e contras de diferentes técnicas de moldagem, mas nenhum consenso da melhor técnica ainda foi descrito.Objetivo Este estudo avaliou a exatidão de modelos de gesso confeccionados por diferentes técnicas de moldagem, moldeiras e materiais.Material e método 10 pacientes foram selecionados e 20 moldes dos dentes #13 até #16 foram realizados utilizando técnicas simultânea (SS) e de dois passos, realizados com moldeiras parciais metálicas e individuais de resina acrílica, silicones de adição e condensação. Gesso tipo IV foi usados para os vazamentos. Três fotografias de cada paciente (baseline), assim como dos seus respectivos modelos de gesso foram realizadas e sua área foi então mensurada, na porção vestibular. Comparações de valores de área entre os grupos experimentais e o baseline foram performadas. Os dados mostraram aderência a curva normal, sendo submetidos ao teste 3-way ANOVA/Bonferroni (α=.05).Resultado As técnicas produziram diferenças significativas (P=0.02).Técnica simultânea foi mais precisa que a BUR (P=0.0003; 95=1,22 a 5.98), mas ambas resultaram em modelos similares àqueles feitos por meio das técnicas de PVC, MOV e sem NR, que foram similares entre si (P>0.05).Conclusão Técnica simultânea demonstrou valores absolutos similares àqueles demonstrados pelo baseline.
Efeito de técnicas, moldeiras e materiais na exatidão de moldagens odontológicas.
Keywords: Dental impression materials; silicone elastomers; dental impression technique; measurements, methods and theories; Materiais para moldagem odontológica; elastômeros de silicone; técnica de moldagem odontológica; medidas, métodos e teorias